Characteristics of Production Factors and Production of Zero Tillage System Rice Farming - Mukhlis Mukhlis; Iis Ismawati; Nova Sillia; Siska Fitrianti; Indria Ukrita; Raeza Firsta Wisra; Hidayat Raflis; Riva Hendriani; Latifa Hanum; Hasan Ibrahim; Sri Nofianti; Andrik Marta; Nila Sari (Postgraduate, University of Mataram, 2024)
Zero tillage system is able to prepare the land for plants to grow and produce well by paying attention to the ecological balance of the environment, especially water and soil. The purpose of this study was to determine the characteristics of production factors and production characteristics of rice paddy farming with no-tillage system. This research used descriptive method, conducted in Taram village, Harau sub-district. Sample determination using snowball sampling method, with a total sample of 50 farmers. Data collection by interview using questionnaires for primary data and documentation method for secondary data. Data analysis used qualitative descriptive analysis with a triangulation approach. The results showed the characteristics of production factors include: paddy field area 0.25 - 2.0 ha, seed requirement 8 - 60 kg/acre, compost fertiliser 0.25 - 2 tonnes/acre, Urea fertiliser 25 - 200 kg, NPK Phonska fertiliser 25 - 200 kg, herbicide 1 - 3 litres, insecticide 1 - 2 litres, labour consists of labour within the family and labour outside the family, including: Labour and female labour, and capital consists of cash, hoes, and knapsack sprayers. The amount of farm labour can be reduced by up to 145%, especially in land preparation activities, because there is no tillage and only spraying of residual rice stalks and weeds. Rice production characteristics: Total production of 800 - 6,200 Kg/acre, with an average of 2,262.80 Kg. The selling price of rice production was IDR 7,500/kg - IDR 7,800/kg, with an average of IDR 7,710/Kg.